The complete chloroplast genome of Tetraena mongolica (Zygophyllaceae), an endangered shrub endemic to China. Issue 1 (2nd January 2019) - Ma, Xiao; Chang, Jiyang; Li, Zhanghai; Zhai, Wei; Yu, Xianxian; Feng, Yanlei
Abstract: Tetraena mongolica, an endangered shrub, is endemic to China’s western Inner Mongolia. Here we have reported its complete chloroplast genome with a length of 106, 288 bp. The inverted repeat regions just retained 4315 bp. The genome encodes a total of 98 predicted genes, including 64 protein-coding genes, 30 transfer RNA genes and 4 ribosomal RNA genes. Fifteen genes, including infA, rps16, ycf1, ycf2 and all the 11 ndh genes, were probably lost from the genome. The clpP and rps12 lost one intron, respectively. All these characters show T. mongolica is a special taxon worth to be further studied.